ANALISIS HASIL BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA BERBASIS MEDIA WORDWALL PADA ERA GLOBALISASI DI KELAS II SDN SOCAH 2 - Dewi Febriyanti; Muttaqina Mafaza; Dwi Maulidia Suciati; Ika Dian Rahmawati (STKIP Subang, 2026)
In the fast-moving digital era shaped by globalization, education has increasingly shifted toward technology-based learning tools. Wordwall is one such interactive platform that transforms educational content into engaging digital activities. This research explored how Wordwall influences the mathematics performance of second-grade students at SDN Socah 2, particularly in addition and subtraction operations within 20. The study adopted a quantitative pre-experimental design with a One Group Pretest-Posttest approach. All 27 students in the class were included using a saturated sampling method. Data were gathered through a 12-question multiple-choice test and analyzed using descriptive statistics, the Shapiro-Wilk test, and Paired Sample t-Test via SPSS 26. Results revealed a noticeable rise in average scores from 55 before treatment to 80 afterward. The statistical test also showed a significance value of 0.000 (<0.05), confirming a meaningful difference after implementing Wordwall. Overall, the platform proved to be effective in improving mathematics learning outcomes while making the learning process more engaging.